Biliary peritonitis due to permeation: analysis Quím Farm. Elisa Balea - Bonilla, Carlos; Mesa, Guillermo; Surraco, José L; Ospina, Tulio; Arios Pressa, C (Cirugía del Uruguay, 1972)
The paper refers to the experimental work carried on with 34 dogs with participation -combining the most common incriminatory factores- of ethiopathogenesis of biliary peritonitis due to permeation. Results obtained point to lesiona! polimorfism in the same experimental conditions, thus we have ethiopathogenical variability which fact should be taken into consideration for a rational therapy,